Case Report: LATE-PRESENTING NEUROFIBROMATOSIS TYPE 1 COMPLICATED BY MALIGNANTTRANSFORMATION AND MULTIORGAN METASTASIZE: A RARE CASE REPORT - Dhiya' Fathiyyah Zen; Intan Dwikarlina; Dessika Rahmawati (Majalah Kesehatan, 2026)
Neurofibromatosis 1 (NF-1) is a rare genetic disorder characterized by a risk of benign and malignant tumors. NF-1 usually arises in childhood. Hence, the incidence of adult-onset NF-1 is important to further discuss. This case report aims to describe the clinical presentation and advanced complications in a 59-year-old patient with suspected neurofibromatosis Type 1 presenting with decreased consciousness and pathological fractures associated with metastatic progression. We report a 59-year-old woman presenting with a gradual loss of consciousness for two months, left arm pain for three months, and a history of multiple lumps and café-au-lait spots since childhood. Physical examination revealed delirium, multiple neurofibromas, freckles, and a fracture of the left humerus. Imaging later demonstrated metastases to the brain, lungs, and bones. This case highlights the malignant potential of NF-1-associated tumors in adults, particularly the risk of multi-organ metastases in long-standing lesions. Diminished level of consciousness may occur due to the transformation of the tumor to malignant, resulting in metastases to the brain. Lung metastases can be identified on radiological findings as nodules. Long bone dysplasia will enhance the risk of pathological fractures in NF-1 patients. Examination of tumor markers, radiology, and histopathology is necessary for diagnosis. Early recognition, vigilant monitoring, and multidisciplinary management are essential to optimize outcomes and prevent fatal complications.